Survey of Various Mobility Models in VANETs (International Journal of Engineering and Computer Science, 2014)
Ad-hoc networking is regarded as an adequate solution to cooperative driving between communicating cars on the road. Deploying and testing these networks, usually known as Vehicular Ad-hoc Networks (VANETs), involves a high cost in the real world, so simulation is a useful alternative in research. In this paper, we discuss five major categories of various Mobility Models that is Entity, Group, Urban, City-Section and Realistic Mobility models for simulation of VANET as a critical aspect in a simulation study of VANETs, is the need for a mobility model which reflects, as close as possible, the real behaviour of vehicular traffic. Our work provides a sound starting point for further understanding and development of more realistic and accurate mobility models for VANET simulations.